Influence of competitive lifting tasks on plasma concentration of biochemical cardiac markers - Tschan, H. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The fear of damage to the cardiovascular system has led most exercise specialists to urge against any breath holding during resisted exercise. Possible detrimental effects include an increase in ventricular diastolic pressure and wall stress, possibly leading to unfavourable remodelling, myocardial ischemia and malignant arrhythmia. Circulating levels of the specific cardiac marker NT-proBNP reflect ventricular diastolic wall stress and are strongly related to mortality. The purpose of this study was to evaluate the effects of static and heavy lifting tasks (weightlifting and power-lifting exercises) on the plasma concentration of NT-proBNP a levels and on other biochemical cardiac markers in trained weightlifters. Methods: 12 healthy well trained weightlifters (national class) performed 6 sets of 6 lifting exercises (snatch, clean, jerk, squat, deadlift, bench-press) with the goal to lift as much weight as possible. Blood samples were drawn from each subject 1 hour before the exercise training as well as immediately after finishing the exercise test and 2 hrs post-exercise. For detection of myocardial and skeletal muscle damage cardiac Troponin I (cTnI), total creatine kinase activity (CK) and myoglobin (Myo) were measured. Serum concentrations of cTnI and myoglobin were measured by immunassays total CK activity by routine photometric assay. For detection of myocardial overload NTproBNP was analyzed within 24 hours using an electrochemiluminescence immunoassay. A one-way ANOVA with repeated measures was used to detect changes over time. The Tukey Honestly Significant Differences (HSD) post-hoc test was used to determine the location of differences when significant main effects were detected. Results: Beside cTnI all markers showed significant elevations (p < 0.05-p<0.001) over the time course of the 3 blood draws. A significant percentage of laboratory parameters analyzed in this study (CK and Myo) were outside the reference ranges. However, the sensitive and specific biochemical markers for detecting myocardial damage (cTnI and NT-proBNP) stayed within the reference ranges and tended to decrease toward baseline levels already 2 hrs after exercise training. Conclusion: From the present study it would appear that heavy resistance exercise is well tolerated by experienced weightlifters without showing any evidence that lifting tasks damages the myocardium. The elevation of the non-specific markers (CK and Myo) may reflect a transient inflammation-like response (mild tissue trauma of the skeletal muscles) following the very intense acute exercise.